2015
DOI: 10.1149/2.0601506jes
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Free Electrolyte for Lithium Ion Batteries Containing γ-Butyrolactone and Methyl Butyrate

Abstract: A novel carbonate free electrolyte, 1 M lithium difluoro(oxalato) borate (LiDFOB) in 1:1 gamma-butyrolactone (GBL)/methyl butyrate (MB), has been compared to a standard electrolyte, 1 M LiPF 6 in 1:1:1 EC/DMC/DEC, and a 1 M LiDFOB in 1:1:1 EC/DMC/DEC electrolyte. The conductivity of 1 M LiDFOB in GBL/MB is higher at low temperature, but slightly lower at higher temperature compared to the standard electrolyte. The 1 M LiDFOB in GBL/MB electrolyte has comparable cycling performance to the standard electrolyte, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Researchers have confirmed that, at 1.7 V and below, in carbonate-based electrolytes [98], the reduction products of LiDFOB (e.g. lithium oxalate, other oxalate containing species, and borates [98,101]) dominate the SEI composition [97]. The SEI is thicker (the impedance of the cell is higher as well) as compared with a LiPF6-containing EC-based electrolyte at low temperature [101] but helps reaching good cycling retention of graphite at room temperature in SL:DMC-electrolyte [92].…”
Section: Alternative LI Saltsmentioning
confidence: 93%
See 1 more Smart Citation
“…Researchers have confirmed that, at 1.7 V and below, in carbonate-based electrolytes [98], the reduction products of LiDFOB (e.g. lithium oxalate, other oxalate containing species, and borates [98,101]) dominate the SEI composition [97]. The SEI is thicker (the impedance of the cell is higher as well) as compared with a LiPF6-containing EC-based electrolyte at low temperature [101] but helps reaching good cycling retention of graphite at room temperature in SL:DMC-electrolyte [92].…”
Section: Alternative LI Saltsmentioning
confidence: 93%
“…lithium oxalate, other oxalate containing species, and borates [98,101]) dominate the SEI composition [97]. The SEI is thicker (the impedance of the cell is higher as well) as compared with a LiPF6-containing EC-based electrolyte at low temperature [101] but helps reaching good cycling retention of graphite at room temperature in SL:DMC-electrolyte [92]. In alkyl dinitrile solvent mixtures such as ADN:DMC, 99.9% efficiency has been reached for graphite (in combination with FEC), whereas ADN and alkyl nitriles in general are usually detrimental for SEI formation [102].…”
Section: Alternative LI Saltsmentioning
confidence: 99%
“…This is clearly due to more stable interfaces in LiDFOB cells. Indeed, it is known that LiDFOB allows, in some cases, graphite cycling in EC-free electrolyte [26], due to its own reduction, prior to other electrolyte components at ca. 1.8 V [21].…”
Section: Graphite Electrode Rate Capabilitymentioning
confidence: 99%
“…Attempts to solve these problems have been made by replacing EC with other carbonate‐based solvents such as ethyl methyl carbonate (EMC) . These electrolytes do, however, not form as stable SEI layers as EC does, and various SEI‐forming electrolytes and additives have therefore been investigated to develop EC‐free electrolytes …”
Section: Introductionmentioning
confidence: 99%
“…[2,3] These electrolytes do, however, not form as stable SEI layers as EC does, and various SEI-forming electrolytes and additives have therefore been investigated to develop EC-free electrolytes. [5][6][7][8] Propylene carbonate (PC) has a far higher dielectric constant than the common carbonate solvents used in LIB electrolytes, and is therefore ideal as a replacement for EC. [9] The melting point of PC is far lower as compared to EC, which is also why it previously has been a part of EC-containing electrolytes intended for low temperatures.…”
Section: Introductionmentioning
confidence: 99%